The Role of Embryonic Chick Muscle Cell Culture in the Study of Skeletal Myogenesis - Costa, Manoel L.; Jurberg, Arnon D.; Mermelstein, Claudia (Frontiers in Physiology, 2021)
The mechanisms involved in the development of skeletal muscle fibers have been studied in the last seventy years and yet many aspects of this process are still not completely understood. A myriad of in vivo and in vitro invertebrate and vertebrate animal models has been used for dissecting the molecular and cellular events involved in muscle formation. Among the most used animal models for the study of myogenesis are the rodents rat and mouse, the fruit fly Drosophila, and the birds chicken and quail. Here, we describe the robustness and advantages of the chick primary muscle culture model for the study of skeletal myogenesis. In the myoblast culture obtained from embryonic chick pectoralis muscle it is possible to analyze all the steps involved in skeletal myogenesis, such as, myoblast proliferation, withdrawal from cell cycle, cell elongation and migration, myoblast alignment and fusion, the assembly of striated myofibrils, and the formation of multinucleated myotubes. The fact that in vitro chick myotubes can harbor hundreds of nuclei, whereas myotubes from cell lines have only a dozen nuclei demonstrates the high level of differentiation of the autonomous chick myogenic program. This striking differentiation is independent of serum withdrawal, which points to the power of the model. We also review the major pro-myogenic and anti-myogenic molecules and signaling pathways involved in chick myogenesis, in addition to providing a detailed protocol for the preparation of embryonic chick myogenic cultures. Moreover, we performed a bibliometric analysis of the articles that used this model to evaluate which were the main explored topics of interest and their contributors. We expect that by describing the major findings, and their advantages, of the studies using the embryonic chick myogenic model we will foster new studies on the molecular and cellular process involved in muscle proliferation and differentiation that are more similar to the actual in vivo condition than the muscle cell lines.